On generalized derivations involving prime ideals with involution - Rehman, Nadeem ur; Alnoghashi, Hafedh M.; Hongan, Motoshi (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 512.5 We study the structure of the quotient A/P, where A is any ring with involution * and P is a prime ideal of A. With an aim to construct a ring with involution of this kind, we study the behavior of generalized derivations satisfying the algebraic identities involving prime ideals. As a consequence, currently existing results in this field are enhanced.